Planejamento reverso em implantodontia: relato de caso clínico - Amoroso, Andressa Paschoal [UNESP]; Gennari Filho, Humberto [UNESP]; Pellizzer, Eduardo Piza [UNESP]; Goiato, Marcelo Coelho [UNESP]; Santiago Júnior, Joel Ferreira [UNESP]; Villa, Luiz Marcelo Ribeiro [UNESP] (My University, 2012)
The oral rehabilitation has achieved great prominence in the dental implant, especially in the cases of reposition of units dental elements, so it is possible to replace each missing element to implant into your space where the tooth was loss. The reverse planning is fundamental to an appropriate rehabilitation, because promote the elimination of problems that might compromise the aesthetics and function of future dental implants. The objective of this study was to report the treatment plan for a patient in need of oral rehabilitation with implant dental prosthesis, using indications and techniques based on the literature, emphasizing the importance of reverse planning. We conducted an osseointegrated implant surgery using the principles of a connect procedure, thus allowing their successfully installing increasing the predictability of treatment. It is concluded that the success of rehabilitation treatment is directly related to the initial planning, a correct clinical approach and an integrated multidisciplinary team.

As reabilitações orais tem atingido grande destaque na implantodontia, principalmente quando se trata de elementos unitários a serem repostos, pois desse modo é possível substituir cada elemento perdido com implante no respectivo espaço onde houve a perda dental. O planejamento reverso do tratamento reabilitador é de suma importância, promovendo a eliminação de problemas que possam comprometer a estética e função das futuras restaurações implantossuportadas. Assim, o objetivo do presente trabalho foi relatar o plano de tratamento de uma paciente que necessita de reabilitação oral com próteses implantossuportadas, seguindo técnicas e indicações baseadas na literatura, enfatizando a importância do planejamento reverso. Realizou-se uma cirurgia com implantes osseointegráveis seguindo os princípios de uma correta instalação, ampliando-se a previsibilidade de tratamento. Concluiu-se que o sucesso do tratamento reabilitador está diretamente relacionado com o planejamento inicial, uma correta abordagem clínica e uma equipe multi-integrada.
Reverse planning in dental implant: case report
Keywords: Implantes dentários; Biomecânica; rótese dentária; Prótese dentária fixada por implante; Dental implants; Biomechanics; Dental prosthesis; Dental Prosthesis implant-supported